2012
DOI: 10.1002/pen.23380
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and phase behavior of blends of polysulfone‐based polymers with phosphorous‐containing smectic‐A liquid crystals

Abstract: Preparation and experimental studies on the phase transitions and morphology of novel polymer-dispersed liquid crystal (PDLC) mixtures of polysulfone UDEL-3000 (PSU) or its derivatives (chloromethylated polysulfone or polysulfone containing lateral phosphaphenanthrene substituent) and a phosphorus-containing liquid crystalline polymer (LCC) that exhibit isotropic/nematic/smectic-A mesophase transition were performed. The mesomorphic properties of PDLC have been investigated by differential scanning calorimetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…TGA analyses were per-formed to quantify the amount of E7 encapsulated in the polymer particles [41]. The prep-aration and experimental studies of phase transitions and morphology of new PDLC sys-tems based on Udel-3000 polysulfone (PSU) or its derivatives (chloromethylated PSU or PSU with a phosphaphenanthrene side substituent) and a phosphorus-containing LC polymer (LCP) were evaluated by Tachita et al [42]. These researchers showed that the presence of the phosphorus atom in the structure of the LCP and also in the polymer matrix, based on phosphorylated PSU, improved the key properties such as flame retardancy, thermal stability, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…TGA analyses were per-formed to quantify the amount of E7 encapsulated in the polymer particles [41]. The prep-aration and experimental studies of phase transitions and morphology of new PDLC sys-tems based on Udel-3000 polysulfone (PSU) or its derivatives (chloromethylated PSU or PSU with a phosphaphenanthrene side substituent) and a phosphorus-containing LC polymer (LCP) were evaluated by Tachita et al [42]. These researchers showed that the presence of the phosphorus atom in the structure of the LCP and also in the polymer matrix, based on phosphorylated PSU, improved the key properties such as flame retardancy, thermal stability, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The first polymer is polysulfone, recognized as good insulator, transparent, which has high light transmittance, hydrolytic stability, resistance at heat and chemicals, biocompatibility and so on. All these properties enable it to be used in many applications, as pure polymer or as matrix for composite materials [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of 9,10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) or its derivatives has been shown to significantly enhance the flame retardancy of epoxy resins . Our group has been focused on the design and synthesis of phosphorus‐containing monomers and/or polymers, especially derivatives of DOPO, exhibiting excellent flame retardant properties . The main advantage of such systems is that the flame retardancy can be improved at concentration lower than 3 wt % phosphorus.…”
Section: Introductionmentioning
confidence: 99%